Experiences of Military Youth During a Family Member's Deployment: Changes, Challenges, and Opportunities. (May 2015) - Knobloch, Leanne K.; Pusateri, Kimberly B.; Ebata, Aaron T.; McGlaughlin, Patricia C.
The deployment of a family member can be very distressing for military children, but it also can supply opportunities for growth. This study addresses calls for research on the changes, challenges, and opportunities facing youth during a family member's tour of duty. It uses the relational turbulence model to frame research questions about how children experience a family member's deployment. Participants were 33 military youth ranging from 10 to 13 years of age who completed one-on-one, semistructured interviews. They reported several changes to family life (Research Question 1), challenges of deployment (Research Question 2), and opportunities of deployment (Research Question 3). The results contribute to the literature by advancing theory, by providing insight into children's experiences in their own words, and by suggesting practical guidelines for helping youth navigate a family member's deployment.